Three new species of Polypedilum Kieffer (Diptera: Chironomidae) from Neotropical region - Pinho, Luiz Carlos; Fusari, Lívia Maria; Lamas, Carlos José Einicker (Zootaxa, 2015)
Three new species of Polypedilum from Brazil, belonging to subgenera Tripodura and Pentapedilum are described and illustrated. P. (Pe.) puri sp. n. and P. (Tr.) guato sp. n. are described based on male adults and P. (Tr.) kadiweu sp. n. on male adult, pupa and larva.